Kepercayaan Diri dan Komunikasi Matematis Melalui Project-Based Learning - Fahrurrozi Fahrurrozi; Zoatul Wardi (Jurnal Inovasi Matematika, 2020)
The purpose of this study is to improve the students' self-confidence and mathematical communication by implementing Project-BasedLearning in the semester VII. This type of research was action research with two cycles. The research instrument consisted of learning tools and data collection instruments in the form of tests of mathematical communication skills and student self-confidence questionnaires. Data analysis used was descriptive qualitative narrative analysis and descriptive statistical quantitative data analysis. Based on the data finding, it was faound that: 1) The learning process had improved seen from the observations of the teaching and learning process, and 2) Mathematical communication skills and student confidence had increased.